IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI MATERI DAERAHKU KEBANGGANKU KELAS V SD NEGERI 4 ARCAWINANGUN - Wahyuni, Meida Tri; Badarudin, Badarudin (Consilium: Education and Counseling Journal, 2024)
Differentiated learning is an approach that considers the individual needs of students in terms of speed, learning style, and level of understanding. Differentiated learning is relatively new, so there are still many teachers who do not understand how to implement differentiated learning. The purpose of this study is to describe the Implementation of Differentiated Learning of My Regional Pride Material in Grade V of SD Negeri 4 Arcawinangun. The research method used is descriptive qualitative. Data collection was carried out by conducting observations, interviews and documentation of fifth grade teachers and students of SD Negeri 4 Arcawinangun. Based on the results of the research that has been carried out, the implementation of differentiated learning consists of 1) initial diagnostics to understand student needs with a focus on the components of content, process, product, and learning environment, 2) Differentiated learning planning, 3) Implementation of differentiated learning, 4) Evaluation and reflection. Keywords: Implementation, Learning, Differentiation